Interleukin-11 - its role in the vicious cycle of inflammation, periodontitis and diabetes: A clinicobiochemical cross-sectional study - Rohit Prasad; Aganashini Suchetha; Puzhankara Lakshmi; Mundinamane Basawalingappa Darshan; Sokke Mallikarjuna Apoorva; Gulabdas Bharwani Ashit (Wolters Kluwer Medknow Publications, 2015)
Context: Interleukin-11 (IL-11) is a multifunctional cytokine with a probable regulatory role in the inflamed periodontal tissue. It has also been shown to inhibit the production of potent proinflammatory cytokines like tumor necrosis factor-alpha, IL-6 and IL-1β in vitro. Type 2 diabetes mellitus, which demonstrates an increase in proinflammatory cytokines, might hypothetically, display a decrease in the levels of IL-11, which down-regulates synthesis of the proinflammatory cytokines. Aims: This clinicobiochemical cross-sectional study was undertaken to try to interpret the link between IL-11, diabetes and periodontitis and to explore the probable protective role of IL-11. Materials and Methods: A total of 90 patients were included in the study and were divided into five groups based on community periodontal index scores and diabetes status. Probing pocket depth and clinical attachment level were measured in all the subjects. Gingival crevicular fluid (GCF) was collected from all the participants using micropipettes and blood samples were collected from subjects in Groups III, IV and V, for analysis of glycated hemoglobin. IL-11 levels were measured in GCF samples by enzyme-linked immunosorbent assay. Statistical Analysis: The data obtained were subjected to statistical analysis. Results: The GCF IL-11 levels decreased from periodontal health to disease and in periodontitis patients with type 2 diabetes with decreasing glycemic control. Conclusions: Interleukin-11 may play an important role in the modulation of immune response via the reduction of proinflammatory cytokine production and periodontal tissue damage. It was seen in this study that IL-11 could be detected in GCF and the levels of IL-11 in GCF decreased progressively from healthy to periodontitis sites. IL-11 levels were significantly lower in chronic periodontitis group when compared to gingivitis group. The decrease in the levels of IL-11 probably indicates that both diabetes and periodontitis may play a synergistic role in the suppression of protective host responses. The potential of IL-11 as a probable biomarker of inflammation in both periodontal disease and diabetes mellitus is indicated by the changeability of IL-11 levels with the change in periodontal disease status and glycemic control. Further longitudinal studies are needed to validate IL-11 as a "biomarker of inflammation" in periodontal disease and diabetes progression and to prove its role in the connecting link between periodontal disease and type 2 diabetes mellitus.